ThPP1 gene, encodes an inorganic pyrophosphatase in Thellungiella halophila, enhanced the tolerance of the transgenic rice to alkali stress - Rui He; Guohong Yu; Xiaori Han; Jiao Han; Wei Li; Bing Wang; Shengcai Huang; Xianguo Cheng (Plant Cell Reports, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

ABA pretreatment enhances the chilling tolerance of a chilling-sensitive rice cultivar - Xiang Hongtao; Wang Tongtong; Zheng Dianfeng; Wang Lizhi; Feng Yanjiang; Luo Yu; Li Rui; Li Zhongjie; Meng Ying; Li Wan; Wang Lianmin; Yang Chunjie (Brazilian Journal of Botany, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

The ArfGAP protein MoGlo3 regulates the development and pathogenicity of Magnaporthe oryzae - Shengpei Zhang; Xiu Liu; Lianwei Li; Rui Yu; Jialiang He; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2017)
Summary The ADP ribosylation factor (Arf) and the coat protein complex I (COPI) are involved in vesicle transport. Together with GTPase‐activating proteins (ArfGAPs) and guanine exchange factors (ArfGEFs) that regulate the activity of Arf, they govern vesicle formation, COPI trafficking and the maintenance of the Golgi complex. In an ongoing effort to study the role of membrane trafficking in pathogenesis of the rice blast fungus Magnaporthe oryzae , we identified MoGlo3 as an ArfGAP protein that is homologous to Glo3p of the budding yeast Saccharomyces cerevisiae . As suspected, MoGlo3 partially complements the function of yeast Glo3p. Consistent with findings in S. cerevisiae , MoGlo3 is localized to the Golgi, and that the localization is dependent on the conserved BoCCS domain. We found that MoGlo3 is highly expressed during conidiation and early infection stages and is required for vegetative growth, conidial production and sexual development. We further found that the Δ Moglo3 mutant is defective in endocytosis, scavenging of the reactive oxygen species, and in the response to endoplasmic reticulum (ER) stress. The combined effects result in failed appressorium function and decreased pathogenicity. Moreover, we provided evidence showing that the domains including the GAP, BoCCS and GRM are all important for normal MoGlo3 functions. Our studies further illustrate the importance of normal membrane trafficking in the physiology and pathogenicity of the rice blast fungus.

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Genome re-sequencing analysis uncovers pathogenecity-related genes undergoing positive selection in Magnaporthe oryzae - Jidong Cao; Yongqi Yu; Junkai Huang; Rui Liu; Yan Chen; Suiyan Li; Jun Liu (Science China Life Sciences, 2017)

mtDNA Heteroplasmy in Monozygotic Twins Discordant for Schizophrenia - Hong Li; Rui Bi; Yu Fan; Yong Wu; Yanqing Tang; Zongchang Li; Ying He; Jun Zhou; Jinsong Tang; Xiaogang Chen; Yong-Gang Yao (Molecular Neurobiology, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Genotoxicity and cytotoxicity reduction of the polluted urban river after ecological restoration: a field-scale study of Jialu River in northern China - Jie Sun; Rui Zhang; Long Qin; Haixiao Zhu; Yu Huang; Yingang Xue; Shuqing An; Xianchuan Xie; Aimin Li (Environmental Science and Pollution Research, 2017)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

Demethyleneberberine alleviates inflammatory bowel disease in mice through regulating NF-κB signaling and T-helper cell homeostasis - Ying-Ying Chen; Rui-Yan Li; Mei-Jing Shi; Ya-Xing Zhao; Yan Yan; Xin-Xin Xu; Miao Zhang; Xiao-Tong Zhao; Yu-Bin Zhang (Inflammation Research, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)